Interfacial adsorption of proteins: a neutron reflectivity study - Latter, EG (2012)
Protein adsorption at the solid/liquid interface is of wide ranging importance in many different areas of science such as biomaterial design, the fate of nanoparticles and in the food industry. As a result, many studies have been undertaken with varying foci but there still remains a lack of agreement between many working in this field and fundamental questions regarding the adsorption of proteins at the solid/liquid interface. Neutron reflectivity is a powerful technique for probing the properties of adsorbed layers at interfaces due to its high structural resolution and the possibility of using isotopic substitution to distinguish between components of a mixture. In this work, neutron reflectivity has been used as the primary technique for the investigation of proteins adsorbed sequentially or from a binary mixture. Initially, the adsorption of four proteins (carbonic anhydrase II, lysozyme, human serum albumin and maltose binding protein) onto a clean silica surface was investigated which revealed the importance of electrostatic interactions and entropic contributions to the driving forces for adsorption. Most of the adsorbed layers were described by a 2-layer model with a thinner, denser layer adjacent to the surface and a thick, diffuse layer extending into the bulk solution. The presence of impurities is also shown to have a significant impact on the adsorption of HSA. A study of the HSA/myristic acid system shows that the presence of small amphiphiles can inhibit HSA adsorption and also remove a pre-adsorbed layer. A comparison was made between the protonated and deuterated forms of two proteins, HSA & MBP, showing the deuterated proteins to have a higher affinity for the surface with adsorption occurring in a 3:1 ratio when from a 1:1 mixture. Likewise, d-MBP displaced h-MBP more readily than vice versa in an investigation into the effect of incubation time on the properties of the protein layer. The extent of desorption into protein free buffer is not affected by incubation time but the extent to which d-MBP was displaced by h-MBP showed a clear trend of decreased exchange with increasing incubation time indicating an active exchange process was occurring. This was also observed to a lesser extent for the sequential adsorption of binary protein systems, HSA & LYS and HSA & MBP. When investigating binary protein mixtures the higher propensity for deuterated proteins to adsorb is observed. LYS dominates when adsorbed from a mixture with h-HSA but from a d-HSA & LYS mix both proteins were adsorbed. The marked difference between the adsorption characteristics of perdeuterated proteins and their protonated counterparts provides a good case study for testing the neutron reflectivity technique when investigating systems with more than one component. This thesis assesses the limitations of the methodology of contrast variation for investigating mixtures as well as using different solvent contrasts. A comparison of neutron reflectivity and dual polarisation interferometry (DPI) shows that the two techniques are similar and any small differences can be attributed to the small change in surface chemistry. This comparison also highlights the advantages of DPI; high throughput of samples and detailed information but the restriction to using a 1-layer model limits its use.